Reticulados em toros euclidianos n-dimensionais e em g-toros planos hiperbólicos - Figueiredo, Lilyane Gonzaga (2011)
In this dissertation we study lattices in quotient spaces. The basic quotient spaces are: (1) n-dimensional euclidean tori, obtained from quotient of Rn by discrete groups of isometries ge- nerated by linearly independent translations and (2) hyperbolic °at g-tori (tori of genus g ¸ 2), obtained from quotient of hyperbolic plane by fuchsian groups. In the euclidean environment, the considered lattices are provided of the additive group Z2; while in the hyperbolic case the studied lattices are the geometrically uniform and the cyclic ones.